Demand for democracy in resilient authoritarianism: evidence from rural China. Issue 7 (3rd October 2018) - Guan, Yichen
ABSTRACT: This article investigates the sources of public demand for democratic institutions under authoritarian rule. While a growing body of literature recognizes that in authoritarian polities such as China, economic development does not lead to democratization in a linear fashion, our understanding of the sources of democratization in resilient authoritarianism remains limited. This article provides an empirical test of the three most compelling theories to subsequently emerge: modernization theory, social capital theory, and institutional theory. The results of a survey conducted in the countryside of Zhejiang and Sichuan provinces provide support for the institutional approach in understanding public demand for democracy in rural China, while the modernization theory and social capital theory are shown to be less useful. Specifically, results show that people working in the government system are core supporters of the regime, whereas income, education attainment, social trust, and one's satisfaction with regime institutions turn out to be irrelevant and do not serve as direct sources of public demand for democracy. These results extend our understanding of the complex interaction between an authoritarian regime and its people, shedding new light on the democratic prospects for resilient authoritarianism.